Results of the Bhaktapur Glaucoma Study, Nepal - Thapa, SS; Paudyal, I; Khanal, S; van Rens, G (Nepalese Journal of Ophthalmology, 2013)
Introduction: The Bhaktapur Glaucoma Study is a population-based, cross-sectional and longitudinal study undertaken in one of the districts of Nepal. Objectives: To determine the prevalence of glaucoma in Bhaktapur district, Nepal. Materials and methods: Thirty clusters were randomly selected and a door-to-door census was conducted to identify citizens 40 years of age and older. Four thousand eight hundred individuals fulfilling the eligibility criteria were referred to the base hospital in Kathmandu for a detailed clinical examination. The diagnosis of glaucoma was based upon criteria described by the International Society for Geographic and Epidemiological Ophthalmology (ISGEO). Results: Complete data was available on 3991 subjects (response rate 83.15 %). The mean IOP was 13.3 mm Hg (97.5th and 99.5th percentiles, 18 and 20 mm Hg, respectively) and mean VCDR 0.26 (97.5th and 99.5th percentiles, 0.6 and 0.8 mm Hg, respectively). Seventy-five subjects had glaucoma, an age-sex-standardized prevalence of 1.80 (95 % confidence interval (CI), 1.68 - 1.92). The age-and sex-standardized prevalence of POAG was 1.24 % (CI, 1.14 - 1.34), PACG 0.39 % (CI, 0.34 - 0.45) and secondary glaucoma 0.15 % (CI, 0.07-0.36). The prevalence of glaucoma increased with increase in age and there was no significant difference in gender. Nine eyes were blind and two subjects bilaterally blind from glaucoma. Conclusion: The overall prevalence of glaucoma was 1.9 %. POAG was the most common form of glaucoma. Visual morbidity from PACG, however, was higher. A large majority of the subjects with POAG had not been previously diagnosed and had intraocular pressure within the normal range. Nepal J Ophthalmol 2013; 5(9):81-93 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7832